2013
DOI: 10.1089/hum.2012.094
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Schwannomas Induced by Adeno-Associated Virus-Mediated Delivery of Caspase-1

Abstract: Schwannomas are tumors formed by proliferation of dedifferentiated Schwann cells. Patients with neurofibromatosis 2 (NF2) and schwannomatosis develop multiple schwannomas in peripheral and cranial nerves. Although benign, these tumors can cause extreme pain and compromise sensory/motor functions, including hearing and vision. At present, surgical resection is the main treatment modality, but it can be problematic because of tumor inaccessibility and risk of nerve damage. We have explored gene therapy for schwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Our previously published data have shown that Schwannoma treatment is amenable to a gene therapy approach. That work demonstrated that intra-tumoral injection of an adeno-associated viral serotype 1 vector (AAV1) encoding the pro-apoptotic and pro-inflammatory enzyme caspase-1 under control of the rat Schwann-cell specific promoter, rP0, conferring cell-type specificity to NF2 cells resulted in significant reduction in tumor growth in a xenograft human schwannoma model in nude mice (Prabhakar et al 2013). In the present study, we compared three myelin specific promoters with an overriding goal of identifying the most efficient and selective promoter for use in a schwannoma gene therapy construct.…”
Section: Introductionmentioning
confidence: 99%
“…Our previously published data have shown that Schwannoma treatment is amenable to a gene therapy approach. That work demonstrated that intra-tumoral injection of an adeno-associated viral serotype 1 vector (AAV1) encoding the pro-apoptotic and pro-inflammatory enzyme caspase-1 under control of the rat Schwann-cell specific promoter, rP0, conferring cell-type specificity to NF2 cells resulted in significant reduction in tumor growth in a xenograft human schwannoma model in nude mice (Prabhakar et al 2013). In the present study, we compared three myelin specific promoters with an overriding goal of identifying the most efficient and selective promoter for use in a schwannoma gene therapy construct.…”
Section: Introductionmentioning
confidence: 99%
“…The schwannomas of the patient were resected and the tumor cells were immortalized using the human papilloma virus E6-E7 genes (18). NF2-deficient cells and animal models have contributed significantly to the understanding of the function of the merlin protein.…”
Section: Discussionmentioning
confidence: 99%
“…Direct intratumoral injection of an adeno-associated virus (AAV) vector was used to induce regression of a human NF2 xenograft schwannoma in a mouse sciatic nerve model (Prabhakar et al 2013). The AAV vector encoded caspase-1 (ICE), which can trigger cell death (Croker et al 2015), under the control of a P0 promoter, which is active in myelinating Schwann cells (Shen et al 2011).…”
Section: Examples Of Therapeutic Delivery Of Proteins Via Evsmentioning
confidence: 99%
“…Considering that only a fraction (i.e. about 20%) of schwannoma cells were transduced by the vector injection, it was surprising to achieve almost complete regression of the tumors (Prabhakar et al 2013). One explanation for this may be found in studies showing that ICE is incorporated into EVs, or travel by nanotubes, which can then be taken up by and kill surrounding cells (Sakar et al 2009).…”
Section: Examples Of Therapeutic Delivery Of Proteins Via Evsmentioning
confidence: 99%
See 1 more Smart Citation